Thermo-hydraulic design of a finned tube double-pipe heat exchanger for acetone cooling. - Pérez Sánchez, Amaury; Artigas Cañizares, Elizabeth Elianne; Alvarez Lores, Laura Thalia; Ranero González, Elizabeth; Pérez Sánchez, Eddy Javier (Ingeniería Química y Desarrollo, 2025)
Finned tube double-pipe counter-flow heat exchangers are considered very effective, valuable and advantageous in the heat transfer industry. In the present paper a finned tube double pipe heat exchanger was designed applying a well-known design methodology, in order to cool down 2 kg/s of an acetone stream from 90 ºC to 30 ºC using chilled water available at 5 ºC. Several important design parameters were determined like the cleanliness factor and the number of hairpins, as well as the pressure drop and pumping power of both streams, among others. The heat load had a value of 276,030 W, while a mass flowrate of chilled water of 3.30 kg/s will be needed to cool the acetone stream. Both fluids will flow under turbulent regime inside the heat exchanger. The value of the cleanliness factor was 0.359, and about three hairpins will be needed. The pressure drop of both fluids are below the maximum value established by the heat exchange service, while the chilled water and acetone streams will need a pumping power of 3,662 W and 575 W, respectively.